(untitled) (Revista Argentina de Cirugía, 2026)
Background: Damage control strategy (DCS) is usually used for the treatment of non-traumatic abdominal emergencies. Objective: The aim of the present study was to describe the main causes and pathophysiologic conditions to perform this strategy, the criteria applied and the associated factors and to compare the observed mortality with the expected mortality in the series. Material and methods: We conducted an observational and retrospective study of 118 patients treated with DSC, with secondary peritonitis and severe abdominal bleeding, abdominal compartment syndrome, abdominal or systemic sepsis or both, hypotension and parameters of metabolic acidosis. Several risk factors were analyzed and it was compared observed versus expected mortality (APACHE II). Results: 112 patients presented generalized peritonitis and 6 had severe intra-abdominal bleeding. Mortality was greater in severe mesenteric ischemia (p = 0.002) and was associated with the number of pathophysiologic criteria used for implementation and with white blood cell (WBC) count ≥ 10 000 x mm3 , hemoglobin (Hb) ≤ 9 g/dL, creatinine level ≥ 1.3 mg/dL, pH ≤ 7.25, lactic acid ≥ 2.5 mmol/L, diabetes, ASA score ≥ 4, ≥ 4 operations and open abdomen. The overall observed mortality and expected mortality according to the APACHE II score were 43.1% and 53%, respectively. Conclusions: Mortality was significantly greater in patients with severe mesenteric ischemia, presence of some of the risk factors evaluated and was associated with the number of criteria used for implementation. The observed mortality was non-significantly lower than expected.